Effect of blending ratio on quality of fresh pineapple (Ananas comosus L.) and mango (Mangifera indica L.) juice blends - Kamarul Zaman, A. A.; Shamsudin, Rosnah; Mohd Adzahan, Noranizan (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Quality and alimental contents of single fruit juice can be ameliorated through mixing or blending process with other fruit juices. Pineapple and mango are the most popular tropical fruits in Malaysia with good characteristic taste. Color properties of pineapple and mango juice blends at ratio of 70P:30M; 50P:50M; 30P:70M was evaluated in term of L*, a*, b* hue, Chroma, color difference (ΔE). Blends ratio 70P:30M juice give the best color performance in terms of hue, chroma and ΔE. Physicochemical properties of juice blends ratio of 70P:30M also give more perishable results of pH (4.32) titratable acidity (0.66% malic acid), total soluble solid (13.67), vitamin C (54.25 mg ascorbic acid/100 ml), and turbidity (438 NTU).